The Generation of Pneumoperitonium by DCI Technique - Rizwan Ali Qaiser, Sikandar Hayat Gondal, Tariq Saeed, Hassan Zaheer, Arsalan Sikandar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The safe and effective insertion of a primary port is the first and most crucial & risky of a laparoscopy. Open laparoscopy, optical trocar insertion, direct trocar insertion (DTI) and direct cannula insertion ot traditional technique of insufflation following Veress needle (VN) insertion via the umbilicus. Aim: To assess the safety of DCI technique to generate the pneumoperitonium in our set up. Methodology: This prospective study was conducted at AIMEC sheikhupura from Feb.2019 to Feb.2020. All the150 patients with symptomatic gall bladder disease were admitted. All consecutive patients who underwent successful LC under the care of a single consultant. GA was used to operate in every case. After painting and draping, a 10 mm infra umbilical incision was made. With the use of towel clips, the anterior abdominal wall was raised, and a direct cannula was inserted into the abdominal cavity. All the LC was performed with four-port technique. Three doses of second-generation cephalosporin were administered in every case. Data was entered and analyzed in SPSS. Result: Total 150 patients were included. There were 30(20%) male and 130(80%) female. The mean age was 42.5±12.2 years. Out of 150(100%) patients 18(12%) were having acute gallbladder disease while rest 132(88%) were chronic cases. Most of the operated patients 81(54%) were discharged at 48 hours, 45(30%) at 24hours while rest of the patients stayed longer, including 15(10%) stayed for 72 hours,9(6%) for 96hours and one of the patients who was converted to open procedure for an accessory duct stayed for 7 days. Conclusion: The conclusion of the study that DCI technique to generate pneumoperitonium for laparoscopic procedures remains safe and rapid technique. Keywords: Laparoscopic surgery, DCI technique, pneumoperitonium, gall bladder disease